Simultaneous Equations Modeling for Terrorism, Poverty, and Economic Growth: Evidence from Pakistan - Shaheen, Kanwal; Zaman, Khalid; Mushtaq, Hifza; Ain, Qurat Ul; Naz, Asma; Bibi, Anam; Akhter, Iram; Bibi, Nadia; Kousar, Rizwana (International Journal of Economics and Financial Issues, 2017)
Terrorism is one of the biggest threats for the developed and developing countries that required unified policies to combat with this evil, however, before devising any sustained policies, it is imperative to lookup for country's socio-economic issues that may restrain this effort in vein. This study examines the relationship between terrorism incidence, poverty issues and economic growth in the context of Pakistan by using the time period of 1980-2015, in order to propose an integrated economic framework for long-term sustained growth. The study used time series cointegration techniques, including, unit root, cointegration, robust least square regression, granger causality and impulse response function for robust inferences. The results show that unemployment and population growth both decreases country's economic growth that put a strain on country's sustained efforts for long-term growth. The improvement in the education status of the residents substantially decline the poverty, however, it does not translated in to labor market, where unemployment increases poverty in country. Although, the study results do not show the positive association between unemployment and terrorism incidence in a country, however, it is evident from the results that there is a positive association between education and number of attacks in a country, which support the Krueger and Maleckova's demand side theory of terrorism. Krueger and Maleckova's terrorism demand theory provoked that educated individuals are more preferable to the terrorist organizations due to have a better skills to plan the terrorist activities. The study concludes that Pakistan government should have to provide better education and employment opportunities to reduce the unwanted thoughts of terrorism activities in a country. Keywords: Terrorism incidence, Poverty, Unemployment, Economic Growth, Pakistan. JEL Classifications: C32, I31.